Suitability for salt-lick tourism: A preliminary assessment on the natural saltlicks at Segaliud-Lokan Forest Reserve, Sandakan, Sabah - W S Lim; Andy Russel Mojiol; P M Yip; C Goh; P Liau; Y C Liaw; S V John (IOP Publishing, 2021)
The natural salt-licks are visited by various species of terrestrial mammals, hence ideal for mammal watching, although the suitability for salt-lick tourism is influenced by other factors. Preliminary research was conducted on the suitability of four natural salt-licks for mammal watching in Segaliud-Lokan Forest Reserve (SLFR), Sabah. The camera trapping survey and field assessment were conducted for eight months, and then the assessment criteria applied in this study included the lick accessibility, detection frequency, species richness, viewable activity sighting probability, reliability and visibility on the terrestrial mammals, at a given lick. A total of 12 different mammal species were recorded, where Sambar Deer, Bearded Pig, Banteng, and Bornean Orang-utan were determined as the main visitor species of this study. Among the four selected salt-licks, the rating score of SL50A (Score=1.71) was significantly lower than those of SL50B, SL56 and SL59 (Score=2.57 respectively, χ2 2=6.794, p=0.042), hence highlighting that SL50A was not suitable for conducting mammal watching activity, unlike the other three natural licks at SLFR. The assessment on the compatibility between the supply (mammalian physical availability) and demand (highly anticipated species) was excluded from this research, therefore emphasizing the need to fill up this particular research gap in the future.